A Pragmatic Study of (Im)Politeness Strategies and Institutional Power in Indonesian Hotel Telephone Conversations - Purnomo, Budi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study examines how (im)politeness strategies and institutional power are dynamically negotiated in Indonesian hotel telephone conversations an interactional domain that remains underexplored in pragmatic and hospitality communication research. Drawing on Brown and Levinson’s politeness theory and Culpeper’s impoliteness framework, the analysis investigates not only the types of strategies used but also how front-desk operators reaffirm institutional authority, manage guest dissatisfaction, and perform pragmatic repairs when interactions risk escalating. Data were collected from naturally occurring telephone conversations in several hotels in Surakarta, Indonesia, and analyzed using a qualitative pragmatic approach. The findings show that (im)politeness is an ongoing negotiation shaped by hierarchical service roles, shifting communicative goals, and institutional expectations. Operators predominantly employ positive and negative politeness to maintain professionalism, yet they occasionally shift to off-record strategies, withholding, or mitigated impoliteness to indirectly enforce hotel regulations or handle guest resistance. These moves are typically followed by face-restoring acts to re-establish interactional harmony and protect both individual and institutional face. The study demonstrates that (im)politeness in hotel discourse functions simultaneously as relational management and institutional power performance. Pedagogically, the findings offer insights for developing ESP materials that enhance pragmatic competence in hospitality service communication.